Optimal One-Shot Detection of Preambles with Frequency Offset - Würll, René; Robert, Jörg; Kilian, Gerd; Heuberger, Gerd (International Symposium on Advanced Networks and Telecommunication Systems, ANTS, 2019)
Unidirectional low power wide area network (LP-WAN) transmissions originating from energy-constrained sensor nodes can only be detected once at the receiver or the transmitted information is lost forever. The usually low-budget transmitters are not synchronized with the receiver and have a significant frequency offset. Hence, we design an optimal detector that maximizes the probability of detection with a hypothesis testing approach using a likelihood ratio test (LRT). The theoretically optimal detector is simulated but not implementable. For practical applications, we present approximated detectors, which are very close to the ideal performance.
CRIS-Team Scopus Importer:2019-06-04
Keywords: Frequency offset; Hypothesis testing; Preamble; Signal acquisition; Synch word